RIMAPS Analysis as a Tool to Elucidate Ascospore Ornamentation Pattern - Romero, S. M. (2014)
Fungal spores frequently present marked or sculptured surfaces; this feature is commonly referred as ornamentation. The presence of surface bars, lines, spines, warts, etc. generally constitutes an important taxonomical diagnostic feature. On the other hand, the distribution pattern of ornamentation units on spore surface is critical as well. The focus of the present work has been placed on ascospores ornamented with conical processes called spines. The objective was to apply RIMAPS to distinguish whether surface ascospore spines were distributed describing concentric rings or spirals, unrevealed patterns to the naked eye.